Go Delivery in Producing Online-Based Police Records (SKCK) to Achieve South Sumatra Polda Service Performance - Ahmad Luthfi; Kgs M. Sobri; Andries Lionardo; Raniasa Putra (Perspektif: Jurnal Ilmu-ilmu Sosial)
This study aims to examine and deploy an online document delivery service, named "GO DELIVERY," for processing Police Record Certificates (SKCK) at the South Sumatra Regional Police. The research follows an information technology-based system development approach, encompassing analysis, design, implementation, and evaluation phases. The analysis phase involves studying the manual SKCK process at the South Sumatra Regional Police and identifying encountered issues. Subsequently, in the design phase, a GO DELIVERY system is conceptualized, enabling applicants to submit SKCK applications online through a designated platform. Implementation entails developing the necessary applications and infrastructure to efficiently and securely support document delivery services. Finally, an evaluation assesses the GO DELIVERY service's efficacy in enhancing SKCK processing efficiency and quality. Results indicate that implementing GO DELIVERY has indeed enhanced service performance, reducing SKCK acquisition time, increasing applicant satisfaction, and optimizing resource utilization at the South Sumatra Regional Police. These findings provide a foundation for similar service development across governmental bodies, ultimately enhancing overall public service efficiency and effectiveness.